Associations of CYP4A11 gene–gene and gene–smoking interactions with essential hypertension in the male eastern Chinese Han population. (4th July 2017) - Zhang, Huimin; Jin, Limin; Mu, Tonglu; Fan, Yingying; Zhang, Haiyang; Zhu, Yuhua; Mao, Xujie; Li, Rong; Tang, Siyuan
ABSTRACT: Objectives : The aim of this study was to investigate the impact of CYP4A11 single-nucleotide polymorphisms (SNP), additional gene–gene and gene–environment interactions on essential hypertension (EH) risk. Methods : A total of 1648 participants (788 males, 860 females), with a mean age of 56.1 ± 14.1 years old, were selected, including 820 EH patients and 828 normotension subjects. Logistic regression was performed to investigate association of SNPs within CYP4A11 gene with high DBP, high SBP and EH risk, and generalized multifactor dimensionality reduction (GMDR) was used to analyze the gene–gene interaction and gene–smoking interaction. Results : Logistic regression analysis showed that EH risk was significantly higher in carriers of C allele of the rs1126742 polymorphism than those with TT genotype (TC+CC versus TT, adjusted OR (95%CI) = 1.56 (1.24–1.91). In addition, we also found that EH risk was also significantly higher in carriers of G allele of the rs3890011polymorphism than those with CC genotype (CG+ GG versus CC, adjusted OR (95%CI) = 1.31 (1.15–2.03). GMDR analysis indicated a potential gene–gene interaction between rs1126742 and rs3890011 and a gene–environment interaction between rs1126742 and smoking. We found that subjects with TC or CC of rs1126742 and CG or GG of rs3890011genotype have the highest EH risk, OR (95%CI) was 2.52 (1.28–3.57). Smokers with TC or CC of rs1126742 genotype have the highest EH risk, OR (95%CI) was 2.20 (1.28–3.40). Conclusions : Gene–gene interaction between rs1126742 and rs3890011 and gene–environment interaction between rs1126742 and smoking were associated with increased EH risk.